Best paediatric evidence; is it accessible and used on-call?. Issue 5 (21st April 2004) - Riordan, F A I; Boyle, E M; Phillips, B
Abstract : Background: Paediatricians wanting to use evidence based medicine (EBM) strategies, need to be able to track down and critically appraise evidence. This requires access to quality filtered resources (for example, Cochrane Library), bibliographic databases (for example, Medline), and paediatric journals. Aims: To determine whether paediatricians have access to these resources when on-call and if they use them to answer clinical questions. Method: A telephone survey of paediatric and neonatal units was performed during November 2001. The "paediatrician-on-call" was asked whether they could access Medline, Cochrane, and paediatric journals, and if they used these when on-call. Results: Paediatric trainees were available in 87 of the 97 units contacted. All except one had access to Medline; although only 56 (64%) could do this near their ward. Eighty had access to Cochrane. Thirteen (15%) could not gain access to their library out-of-hours. All except one department had local guidelines, with 71% having >15 guidelines. Access to any of the top seven "best evidence" paediatric journals varied from 64% to 100%. Only 26% of trainees had read the evidence based section of Archives of Disease of Childhood, Archimedes. Many trainees claimed to use guidelines when on-call (61; 70%), but few used Medline (14; 16%). Conclusions: Paediatric trainees mostly have access to facilities to help them to track down and critically appraise evidence. However, few of them have used it to help make clinical decisions when on-call. Many of the doctors contacted said they used local guidelines as their source of information on-call.